Reading in the structure of the feminist text by some Saudi poets - Al-Saad, prof. Yahya Ahmed Mohammed (Al-Adab Journal, 2020)
This research deals with the compositional and semantic structure of the Saudi feminist poem among some Saudi poets, relying on the descriptive and analytical approach in the study of poetic texts, and the research consists of two parts: the structural level and the semantic level, and the researcher reviewed a number of Saudi feminist texts at each level. Different in formal and semantic construction. The research concluded with several results, including the researcher at the conclusion of the research, as well as proved at the end of the research a number of recommendations that were concluded by a study.